USING MODERN TECHNOLOGIES IN TEACHING AND LEARNING ENGLISH (Modern education and development, 2025)
This article is about the appropriate use of modern technologies in learning and teaching English and about the teacher's self-improvement, sense of responsibility, introducing novelties into lessons, and ensuring the lesson is interesting and lively.